2021
DOI: 10.1371/journal.pone.0260849
|View full text |Cite
|
Sign up to set email alerts
|

Zipf’s laws of meaning in Catalan

Abstract: In his pioneering research, G. K. Zipf formulated a couple of statistical laws on the relationship between the frequency of a word with its number of meanings: the law of meaning distribution, relating the frequency of a word and its frequency rank, and the meaning-frequency law, relating the frequency of a word with its number of meanings. Although these laws were formulated more than half a century ago, they have been only investigated in a few languages. Here we present the first study of these laws in Cata… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(142 reference statements)
1
6
0
Order By: Relevance
“…However, after Zipf's groundbreaking research, one of the most noteworthy findings regarding the rank-frequency law in sizable textual corpora with multiple authors is that the power law proposed by Zipf (Equation ( 6)) must, for the most part, be expanded into a double-power law Montemurro 2001;Williams et al 2015), something related to the small-world structure of the linguistic network (Ferrer-i-Cancho and Solé 2001). In fact, in the case of Catalan, the target language of the present study, the existence of these two Zipfian regimes for Equations ( 4) and ( 6) has already been documented in previous studies for multi-author corpora (Català et al 2021). The structure of the linguistic network means that, in the first regime of low ranks, there is an abundance of function words.…”
Section: Statistical Laws On Meaningsupporting
confidence: 78%
See 3 more Smart Citations
“…However, after Zipf's groundbreaking research, one of the most noteworthy findings regarding the rank-frequency law in sizable textual corpora with multiple authors is that the power law proposed by Zipf (Equation ( 6)) must, for the most part, be expanded into a double-power law Montemurro 2001;Williams et al 2015), something related to the small-world structure of the linguistic network (Ferrer-i-Cancho and Solé 2001). In fact, in the case of Catalan, the target language of the present study, the existence of these two Zipfian regimes for Equations ( 4) and ( 6) has already been documented in previous studies for multi-author corpora (Català et al 2021). The structure of the linguistic network means that, in the first regime of low ranks, there is an abundance of function words.…”
Section: Statistical Laws On Meaningsupporting
confidence: 78%
“…where γ ≈ 1/2 (Català et al 2021). To unify the terminology, we refer to the number of meanings of a word (µ) as the sum of the total number of senses that appear in the dictionary, i.e., what has also been called semantic ambiguity (Hoffman et al 2013).…”
Section: Statistical Laws On Meaningmentioning
confidence: 99%
See 2 more Smart Citations
“…Zipf presented empirical evidence for the first law but derived the second one from theoretical considerations; for a recent analysis, see Ferrer-i Cancho et al (2020). Using newly available databases such as WordNet, linguists have started to study the second law as an empirical subject and found substantial initial support in multiple languages (Piantadosi et al, 2012;Català et al, 2021). For example, Piantadosi et al "argue that ambiguity can be understood by the trade-off between two communicative pressures which are inherent to any communicative system: clarity and ease.…”
Section: Towards Explanation By Pragmatic Normsmentioning
confidence: 99%